Cisco Unity fundamentals - Morgan, Brian (Brian Edward); Gonzalez, Moises; Cioara, Jeremy (Indianapolis, Ind. : Cisco Press, 2005)
"Cisco Unity Fundamentals provides design and administration goals for migrating from PBX to Cisco IP Telephony, as well as working in a mixed PBX/Cisco IP Telephony environment. You will learn about the transition from the traditional model, with separate architectures for voice-mail and e-mail systems, to supporting unified messaging: e-mail, voice, and fax messages delivered to a single inbox. You will also discover common troubleshooting solutions, such as performance monitoring and the importance of data collection for predicting future system requirements"--Resource description p
Cisco unified communications system fundamentals -- Using your Cisco unified communications systems -- Setting up Cisco unified communications -- Unified communications subscribers -- Cisco unified communications system customization -- Cisco unified communications system maintenance -- Understanding Cisco unified communications system hardware -- Cisco unified communications system software -- Cisco unified communications integrations -- Unified communications networking -- Unified communications backup and utilities
Keywords: Telecommunication -- Message processing; Internet telephony; Multimedia communications